Implementation of error correction strategies in middle grade foreign language classrooms - Kozhakhmetova Aidana Talgatkyzy (Progress in Science, 2025)
The comparative analysis of student writing samples from the diagnostic phase and the post-implementation evaluation revealed significant improvements across all error categories. The most notable quantitative findings emerged in several key areas of student performance. Error frequency decreased substantially across all writing tasks, with an overall reduction of 47% when comparing pre-implementation and post-implementation samples. This improvement was not uniform across error types, however, with grammatical errors showing the most significant decrease (56% reduction), followed by organizational errors (49%), lexical errors (43%), and mechanical errors (38%). This pattern suggests that the structured approach to error correction was particularly effective for rule-governed language aspects where explicit instruction and pattern recognition could be most readily applied. The multilingual context of Kazakhstan created both challenges and opportunities for error correction. Many error patterns reflected interference from students' first languages (primarily Kazakh and Russian), particularly in article usage, prepositions, and word order. The coded feedback system helped make these interference patterns explicit, allowing students to develop greater awareness of cross-linguistic differences. Teachers observed that explicitly addressing L1 interference within the error correction framework helped students distinguish between language systems more effectively than general grammar instruction.